Optimisation of cutter geometrical feature for machining orthopedic, trauma and spinal biomaterials implant - Mohd Nawawi, Nurul Husna (2016)
Polyetheretherketones (PEEK) are polymeric based composites that resistance to chemical and radiation, excellent stability in high temperature and biocompatible. It is a semicrystalline polymer which consists of polyaromatic ketones that contributed to toughness and flexibility of its structure. Due to its enhanced chemical and mechanical structure,PEEK has been commercialized as implant components for orthopedic and trauma applications because it is promote non-allergic reactions compared to the metal implants.Generally, implants are fabricated by extrusion and injection molding for a larger scale.However, often for short production runs, it is not economically viable to manufacture by an injection molding. Under such circumstances, it is common to employ a machining process on the PEEK materials to form the components. The requirement for a fine surface roughness poses a major concern in machining of polymeric base materials due to its low thermal conductivity. Surface morphology is a vital factor for medical implants since the cells of the surrounding tissue interact with the underlying substrate on the micro and nanometer scales. For some application such as self-mating articulation cervical disc implants, smooth surface finish is critical so as to minimize the contact friction and wear.Machining performances such as surface roughness and cutting forces especially for polymeric material such as PEEK are directly affected by cutting tool geometry. Most of the cutter geometry employed for machining PEEK was using the same cutter as machining metal which tends to lower its machining performances. Roughed surface,premature tool wear and localized heating are defects that related with machining these polymeric materials. All of these defects are directly related with the tool geometries functions and should be methodically considered. Tool geometries such as helix angle,rake angle, clearance angle and number of flute are important in mechanics of material removal process and significantly affect the machining performances. Thus, this thesis aims to develop new cutter geometry for machining PEEK material to enhance the machining performance and productivity. To achieve the objective, Taguchi and Response Surface Methodology (RSM) experimental techniques were employed for optimizing tool cutter geometry. From the conducted experiment, it shows that a two flutes cutter geometry with a combination of 16.20° rake angle, 30.21° helix angle and 10° clearance angle was the best cutter geometry that produced the lowest resultant force and surface roughness value which are predicted to be 247.434 Newton and 0.633 μm respectively. Meanwhile, the correlation between experimental and predicted solution was significant with the ranges of percentages contribution for resultant force were 92.25% to 97.74% and for surface roughness were 91.74% to 99.52%. The good agreement value between prediction and experimental hence validate the new proposed cutter design optimize the machining performance of PEEK.